2015
DOI: 10.1080/15548627.2015.1115173
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of podocyte autophagy in the progression of diabetic nephropathy

Abstract: Glomerular podocytes are pivotal in maintaining glomerular filtration barrier function. As severe podocyte injury results in proteinuria in patients with diabetic nephropathy, determining the pathogenesis of podocyte injury may contribute to the development of new treatments. We recently showed that autophagy is involved in the pathogenesis of diabetes-related podocyte injury. Insufficient podocyte autophagy and podocyte loss are observed in diabetic patients with massive proteinuria. Podocyte loss and massive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 0 publications
3
72
0
Order By: Relevance
“…We have also revealed the reduced expression of LAMP-1 in the renal cortex by western blotting. The results are in agreement with the data from other researches recorded downregulation of autophagy in diabetic kidneys [4,[23][24][25][26].…”
Section: Suppression Of Renal Autophagy In Diabetes: Markers and Mechsupporting
confidence: 93%
See 1 more Smart Citation
“…We have also revealed the reduced expression of LAMP-1 in the renal cortex by western blotting. The results are in agreement with the data from other researches recorded downregulation of autophagy in diabetic kidneys [4,[23][24][25][26].…”
Section: Suppression Of Renal Autophagy In Diabetes: Markers and Mechsupporting
confidence: 93%
“…In its turn, the loss or damage of podocytes causes dysfunction of the filtration barrier and increases albuminuria [2]. Some recent studies have indicated an emerging role of autophagy downregulation in diabetic podocytopathy [4][5][6]. Autophagy is a cellular recycling process involving self-degradation and reconstruction of damaged organelles and proteins [6].…”
mentioning
confidence: 99%
“…Autophagy was reported to be renoprotective in several animal models such as aging and acute kidney injury models [20]. Recently, autophagy was revealed to be particularly important for the maintenance of podocytes, which have only a limited capacity for regeneration [21]. For example, aging mice, with podocyte-specific deletion of autophagy-related genes, exhibited proteinuria and glomerulopathy [9].…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Furthermore, the highly specialized and terminally differentiated podocytes are unable to proliferate, so autophagy plays an important role in maintaining the normal structure and function of podocytes. 11 Autophagic dysfunction is involved in the loss of the podocytes, resulting in a large amount of proteinuria in DN patients. 12 Autophagy is the major intracellular degradation system by which cytoplasmic materials are delivered to the lysosome and then degraded.…”
Section: Introductionmentioning
confidence: 99%